Input for and output of local governance in rural development - Kim Pollermann; Petra Raue; Gitta Schnaut (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Support for balanced regional development with participatory approaches has a long tradition in EU funding programmes for rural development. LEADER started 25 years ago and now has 2600 Local Action Groups (LAGs). These LAGs collaborate as a kind of a public-private partnership on the basis of an integrated local development strategy and administer own budgets to support projects. To examine the contributions of LEADER to local governance, we can present results from the ex-post-evaluation of Rural Development Programs (2007-2013) in six federal states in Germany. A mixture of qualitative and quantitative methods has been used. In addition first evaluation results are shown for the 2014-2020 funding period, especially from a survey of 115 LAGs in four German federal states. To examine governance matters on the input-side we look at the type and structure of participa-tion while on the output-side we focus on contributions to rural development. On the input-side the involvement of civil society and economy actors was successful, but inade-quate funding conditions for private actors set limitations for their involvement in project imple-mentation. In addition, the LAG-compositions show a lack of underprivileged groups and note-worthy shortfalls in gender representation. Looking at the output-side and the factors favoring the success of governance arrangements like LEADER, the estimations of LAG-managers show that the most important factors are: commit-ment, financial/material resources, involvement of key-personalities as driving forces, level of acceptance/cooperation and support from local/regional political actors. Remarkably, the quality of the local development strategies was rated less important but still relevant.
Conference: Regional Studies Association, Annual Conference 2017: The Great Regional Awakening: New Directions, 4th – 7th June 2017, Trinity College Dublin, Ireland
Keywords: H11; R58; 330; rural development; governance; LEADER; CLLD